Sociology of Law – A Tool for Reflecting Citizenship in a Complex Society - Guibentif, P. (Socio-Legal Trajectories in Europe: Comparative Perspectives from the UK, Germany and beyond, 2023)
The topic of the workshop gives me an opportunity to give an account of the links between three lines of work I did develop throughout my career: (1) defending sociology of law as an academic discipline; (2) defending a certain conception of university; (3) elaborating a theoretical framework aiming at understanding the place of individualities in contemporary democratic societies. - Empirical socio-legal research gave me the opportunity to observe changes concerning the position of individuals throughout the last decades. Comparison between several theories of modern societies, all with a focus on the law, led me to approach these changes as recent steps in a process that goes from the Renaissance to late modernity. These were tools which helped me to analyse processes occurring within the scientific domain, and in which I found myself involved. They helped me participating in the design of programme proposals, which had to be defended in arenas of scientific politics. These debates in politics of science led me to the conviction that the concept of democracy has to be developed out of a certain notion of individualities recognized for their imaginative contribution to the multiple groups to which they belong. At the moment of formulating a theory of modern individuality which is required here, it is time to come back to the sociology of law, and to appreciate to what extent it is likely to strengthen such a theory, and to what extent such a theory could encourage its future developments.